Polish as a foreign language at elementary level of instruction: crosslinguistic influences in writing - Gabrys-Barker, Danuta (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
Being a minority European language, Polish has not attracted the attention of second language research (SLA) very much. Most studies in the area focus on English and other major languages describing variables and process observed in learners’ interlanguage development. This article looks at the language performance of elementary learners of Polish as a foreign language with a view to diagnosing areas of difficulty at the initial stages of language instruction. It is a case study of five learners’ written production after a year of intensive language instruction in the controlled conditions of a classroom. The objective of the study presented here is: (1) to determine the types of error produced in a short translation task at different levels of language (morphosyntactic, lexical); (2) to observe manifestations of crosslinguistic influences between languages the subjects know (interlingual transfer) as well as those related to the language learnt itself (intralingual transfer). The small sample of texts produced does not allow for any generalized observations and conclusions, however, at the level of elementary competence in any foreign language, as other research shows, the amount of individual variation is not the most significant factor. Thus the incorrect forms produced may testify to some more universally error-prone areas of language. The value of this kind of analysis lies in this direct application to the teaching of Polish as a synthetic language. The study also demonstrates the fact that communicative teaching has a limited contribution to make in the case of this family of languages. It suggests that overt and explicit teaching of a synthetic language will give a sounder basis for further development of language competence in its communicative dimension.